HUBUNGAN PEMANFAATAN PERPUSTAKAAN SEKOLAH DENGAN HASIL BELAJAR KELAS XI IIS SMAN 9 PONTIANAK - Novitasari, Novitasari; Achmadi, Achmadi; Firmansyah, Andang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to know the relationship of library school with the assessment of historical lesson  to student at grade XI  IIS of SMAN 9 Pontianak. Method was applied in this research is descriptive method with research relation study. The subject of this research were the 54 student that’s the sample and the data is the sheet answer, student questioner, observation and the interview result of thehistory lesson teacher. The technique of data collecting that applied the direct observation, direct communication, indirect communication, and then documentary study. The tools of collecting data were observation guide, interview guide, questionnaire, note sheet, and some picture while interview, the test of validity questionnaire , questionnaire distribution. To process the data in this research use the persentage formula and simple regression analysis. While result observation data and interview was analys with descriptive analysis. Based on the observation data the correlation finding showed that 0,638 based stipulated condition that score was took between 0,600-0,799 it is bold catagory, the conclution that there are relationship independent  variable (X) with dependent variable (Y) or there are relationship positif  and significant between librarywith the assessment of historical lesson at grade XI IIS of SMAN 9 Pontianak.   Keywords: Library School, The Assessment, HistoricalLesson